2023
DOI: 10.3390/ijerph20042881
|View full text |Cite
|
Sign up to set email alerts
|

Related Factors with Depression and Anxiety in Mastectomized Women Breast Cancer Survivors

Abstract: Breast cancer (BC) is the most common cancer diagnosis with the highest mortality rate worldwide. The aim of this study was to identify factors related to depression and anxiety in mastectomized women BC survivors. A cross-sectional study was conducted with a sample of 198 women diagnosed with BC aged 30–80 years in Mexico. Depression and anxiety were assessed using the 14-item Hospital Anxiety and Depression Scale (HADS). The results showed that 94.44% and 69.18% of the women scored more than eight points on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…The demographic and descriptive characteristics of the 198 women who participated in the study are reported in the following article [ 34 ]. In this case, more variables were taken into account.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The demographic and descriptive characteristics of the 198 women who participated in the study are reported in the following article [ 34 ]. In this case, more variables were taken into account.…”
Section: Resultsmentioning
confidence: 99%
“…For age (<50 years vs. ≥50 years), this cut-off has been justified in the existing literature [ 33 ]. Years since diagnostic or elapsed years (<5 years vs. ≥5 years), this 5-year cut-off has been used and justified in the current literature [ 34 ]. Whether they had knowledge of the diagnosis or not, patients were asked about the information they had regarding their BC (diagnosis, treatment, and prognosis) and reflected on their perception of the information they had(none or little vs. knowledge).…”
Section: Methodsmentioning
confidence: 99%
“…Dampak emosi positif yang ditemukan pada penelitian ini tidak membutuhkan psikoedukasi. Emosi positif dipengaruhi oleh faktor usia (Álvarez-Pardo et al, 2023), stres positif dan koping yang sehat (Bienertova-Vasku et al, 2020). Berdasarkan hal diatas, dapat diidentifikasi bahwa permasalahan emosi negatif pada pasien pasca mastektomi membutuhkan psikoedukasi seperti teknik pernafasan dalam dan relaksasi otot progresif.…”
Section: Permasalahan Emosi Negatifunclassified
“…WHO reports 685000 deaths worldwide and 2.3 million new breast cancer diagnoses in women occurred in 2020 [ 5 ]. According to various pieces of literature, people who are either breast cancer patients or survivors experience varying levels of depression [ 6 - 16 ]. Depression can adversely affect the patients by affecting their will to fight the disease as well as negatively impacting the survivors' quality of life after they have won the battle against breast cancer.…”
Section: Introductionmentioning
confidence: 99%